The Influence of Banking Super Apps on Enhancing Brand Loyalty: A Review of Social Exchange Theory - I Gede Billy Ambara Putra; Yolanda Masnita; Kurniawati Kurniawati; Intan Yuniarti Ningsih (Dinasti International Journal of Education Management And Social Science, 2025)
This research investigates the influence of banking Super App characteristics on customer-brand engagement, brand trust, and brand loyalty through the lens of Social Exchange Theory (SET). As digital banking continues to evolve, Super Apps emerge as comprehensive platforms that integrate various financial services, aiming to enhance user experience and foster long-term relationships. This study specifically examines the roles of perceived fluency, integration quality, and assurance quality in shaping customer perceptions and behaviors. Using Structural Equation Modelling (SEM), data were collected from 298 individuals who regularly use digital banking services. The findings reveal that perceived fluency and integration quality significantly influence customer-brand engagement and contribute to building brand loyalty. In contrast, assurance quality plays a critical role in strengthening brand trust, which subsequently reinforces loyalty. One of the key contributions of this study is the identification of brand trust as a mediating variable between assurance quality and customer-brand engagement. This underscores the importance of building trust through reliable and secure app functions, which can deepen emotional connections with users. Furthermore, the study provides empirical evidence supporting SET in the context of digital banking, illustrating how perceived value and trust can foster reciprocal and sustained interactions between customers and financial institutions. The implications are relevant for banking strategists and app developers seeking to enhance user retention and engagement. Future research is encouraged to explore additional factors such as customer experience, personalization, and technological innovation to enrich the understanding of customer-brand dynamics in the digital finance ecosystem.